2014
DOI: 10.1016/j.omega.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Setting tolerance limits for statistical project control using earned value management

Abstract: Project control has been a research topic since decades that attracts both academics and practitioners. Project control systems indicate the direction of change in preliminary planning variables compared with actual performance. In case their current project performance deviates from the planned performance, a warning is indicated by the system in order to take corrective actions.Earned value management/earned schedule (EVM/ES) systems have played a central role in project control, and provide straightforward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 55 publications
0
43
0
1
Order By: Relevance
“…In these studies, the baseline schedule is considered as a point of reference throughout the execution of the project, and that together with the real-schedule performance and the cost associated with it, are compared relative to the baseline estimates. In the MCS for such project-management studies, the individual activities are given a duration that might deviate from the estimated duration that was used for the construction of the baseline schedule (Vanhoucke 2010b(Vanhoucke , 2011Elshaer 2013;Colin and Vanhoucke 2014). The relation to real-life projects is evident, since only very seldom a project will go exactly as planned in terms of the durations of the individual activities and their associated costs.…”
Section: Focus On the Relative Duration Of Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In these studies, the baseline schedule is considered as a point of reference throughout the execution of the project, and that together with the real-schedule performance and the cost associated with it, are compared relative to the baseline estimates. In the MCS for such project-management studies, the individual activities are given a duration that might deviate from the estimated duration that was used for the construction of the baseline schedule (Vanhoucke 2010b(Vanhoucke , 2011Elshaer 2013;Colin and Vanhoucke 2014). The relation to real-life projects is evident, since only very seldom a project will go exactly as planned in terms of the durations of the individual activities and their associated costs.…”
Section: Focus On the Relative Duration Of Activitiesmentioning
confidence: 99%
“…This will not be considered further, as this is only relevant for when an actual simulation model is proposed. A recent application of linear association in project management simulation can be found in Colin and Vanhoucke (2014). Here, the primary concern lies with the calibration of the inputs to such simulation studies.…”
Section: Focus On the Relative Duration Of Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Narbaev and De Marco (2014) attempted to overcome limitations of the traditional EVM and proposed an earned schedule-based regression model to improve cost estimate at completion. Colin and Vanhoucke (2014) proposed statistical project control procedure which sets tolerance limits to improve discriminative power between progress situations that are either statistically likely or less likely to occur under the project baseline schedule. Lipke et al (2009) also applied statistical methods to EVM and ES performance indexes and found the proposed forecasting method to be suffi ciently reliable.…”
Section: Figure 2 Variances and Indexes Used In Earned Value Managementmentioning
confidence: 99%
“…In this research, the tolerance limits are derived from subjective estimates for the activity durations of the project. Tolerance limits are set for statistical project control using EVM [17].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%